Morphometric variation in the human liver and its clinical implication: a cadaveric study - Kumar, Anil; Siddiqi, Najam; S.Klinkhachorn, Penprapa (Journal of Neonatal Surgery, 2025)
Background: The most frequently encountered morphological variations of the liver include alterations in its form and shape, as well as the presence of accessory lobes, accessory fissures, and atypical ligaments. Awareness of these anatomical anomalies is essential for clinicians in differentiating pathological conditions, for surgeons performing segmental liver resections, and for radiologists when interpreting hepatic imaging findings. Objectives: This study aimed to characterize morphological variations of the liver, perform detailed morphometric analysis, and elucidate their clinical significance. Methodology: Morphological variations of the liver—including alterations in size and shape, the presence of accessory or hypoplastic lobes, and the occurrence of fissures, notches, and grooves—were systematically documented in 42 formalin-fixed specimens. Each liver was examined for external morphology and associated variants, photographed, and the findings were recorded and tabulated. Results: Liver morphometry and morphology in the specimens revealed variable lobe dimensions, frequent accessory fissures, diaphragmatic grooves, and Type 1 predominance, highlighting significant anatomical diversity relevant for surgical and radiological considerations. Conclusion: The findings of this study may aid surgeons and radiologists in minimizing interpretative errors and potential misdiagnoses, while also supporting the selection and planning of appropriate surgical approaches.